2013
DOI: 10.1186/1556-276x-8-225
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced solar energy conversion in Au-doped, single-wall carbon nanotube-Si heterojunction cells

Abstract: The power conversion efficiency (PCE) of single-wall carbon nanotube (SCNT)/n-type crystalline silicon heterojunction photovoltaic devices is significantly improved by Au doping. It is found that the overall PCE was significantly increased to threefold. The efficiency enhancement of photovoltaic devices is mainly the improved electrical conductivity of SCNT by increasing the carrier concentration and the enhancing the absorbance of active layers by Au nanoparticles. The Au doping can lead to an increase of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 47 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…In present experiment, the processes of EPD and doping are similar as that of our previous method in Ref. 12. In order to obtain the uniformity GP sheet solution, the chemical vapor deposition (CVD) GP (1 mg) was first dispersed in analytically pure isopropyl alcohol (IA) (200 ml) using the high power tip sonication for about 1.5 h. For better dispersing the GP, then the further ultrasonic treatment was carried out using a sonic bath for about 3 h. During the dispersing process, a little amount of Mg(NO 3 ) 2 6H 2 O was added into the solution to make the Mgþ absorbed on the surfaces of GP.…”
Section: Field Emission Performance Enhancement Of Au Nanoparticles Dmentioning
confidence: 68%
See 1 more Smart Citation
“…In present experiment, the processes of EPD and doping are similar as that of our previous method in Ref. 12. In order to obtain the uniformity GP sheet solution, the chemical vapor deposition (CVD) GP (1 mg) was first dispersed in analytically pure isopropyl alcohol (IA) (200 ml) using the high power tip sonication for about 1.5 h. For better dispersing the GP, then the further ultrasonic treatment was carried out using a sonic bath for about 3 h. During the dispersing process, a little amount of Mg(NO 3 ) 2 6H 2 O was added into the solution to make the Mgþ absorbed on the surfaces of GP.…”
Section: Field Emission Performance Enhancement Of Au Nanoparticles Dmentioning
confidence: 68%
“…12 The parameters of distance between two electrodes, constant DC voltage, and deposition time for the GP were 1 cm, 100 V, 15 min, respectively. After finishing EDP, the GP emitters were washed with the dilute nitric acid solution and the deionized water, respectively.…”
Section: Field Emission Performance Enhancement Of Au Nanoparticles Dmentioning
confidence: 99%
“…Three features in the measured Nyquist plots are highlighted as the following (Figure f). First, in the highest frequency region, the corresponding value in the x ‐axis stands for R S , which is lowered from 126 to 83 Ω after SnCl 2 coating. The higher carrier density in CNTs introduced by the p‐type doping effect is favorable for reducing R S .…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, introducing functional materials into the CNT‐Si solar cells has proved to be an effective strategy to improve the cell efficiency. To this end, a variety of materials, such as acids, metallocenes, Au nanodots, AuCl 3 , colloidal TiO 2, polymethylmethacrylate, MoO x , and CuCl 2 /Cu(OH) 2 , have been explored, whose functions generally fall into three categories, including 1) chemical doping; 2) antireflection; and 3) acting as functional layers. For example, it was found that those introduced materials could dope CNTs and modulate the work function of CNTs as well as the diode/junction characteristics (e.g., for HNO 3 and Au salt) or act as an antireflection layer to enhance the light absorption and external quantum efficiency (e.g., for TiO 2 and polymethylmethacrylate) .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Since the 1980s, the significant role of dimensionality has been recognized apart from the bulk phase, inspiring the swift development of low-dimensional materials (0D, 1D, 2D). [7][8][9][10] The realm of 0D quantum dots, [11][12][13][14] 1D nanowire, [15][16][17][18][19] nanotube, [20][21][22][23][24] etc., has become hot research spots in succession. However, 2D materials remained to be a silent zone somehow.…”
Section: Introductionmentioning
confidence: 99%